Enhance protection of electronic appliances through multivariate modelling and optimization of ceramic core materials in varistor devices. Issue 27 (25th February 2015) - Dorraj, Masoumeh; Abdollahi, Yadollah; Mohd Said, Suhana Binti; Bin Mohd Sabri, Mohd Faizul; Sairi, Nor Asrina; Meng, Woi Pei; Abouzari-lotf, Ebrahim
Abstract : E-waste comprises discarded low quality protected electronic appliances that annually accumulate a million tons of hazardous materials in the environment. Abstract : E-waste comprises discarded low quality protected electronic appliances that annually accumulate million tons of hazardous materials in the environment. Protection is provided to control unwanted voltages that usually generate in associated electrical circuits by a multi-junction ceramic in a voltage dependent varistor. The ceramic's microstructure consists of ZnO grains that are surrounded by the narrow boundaries of melted specific additives such as Bi2 O3, TiO2 and Sb2 O3 . In fact, the boundaries manage the quality of protection through a certain volume of intrinsic oxygen vacancies transformation which depends on the amounts of the additives. Since these amounts are the ceramic fabrication's initial input variables, the optimization process is capable of improving the quality of the protection (non-linear coefficient) as an output of the varistor devices. In this work, the fabrication was designed and then experimentally performed to calculate the non-linear coefficients of the produced varistors as actual responses. The responses were used to obtain an appropriate model for the fabrication by different semi-empirical methods. Afterward, the models predicted the optimized amounts of the additives which maximized the quality of the varistors. The predicted condition was fabricated as final varistors that were electrically characterized to compare their nonlinear coefficients as the quality indicator. The comparison demonstrated that the optimized amounts of Bi2 O3 (0.5), TiO2 (0.47) and Sb2 O3 (0.21) in mol% provided the very high protective varistor with nonlinear coefficients of 28.1. In conclusion, the optimization, which has industrial scale-up potential, warranties the electronic protection that controls global e-waste.